2021
DOI: 10.1055/s-0040-1718923
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis in Acute and Chronic Cardiovascular Disease

Abstract: The formation of an obstructive thrombus within an artery remains a major cause of mortality and morbidity worldwide. Despite effective inhibition of platelet function by modern antiplatelet therapies, these agents fail to fully eliminate atherothrombotic risk. This may well be related to extensive vascular disease, beyond the protective abilities of the treatment agents used. However, recent evidence suggests that residual vascular risk in those treated with modern antiplatelet therapies is related, at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…The activation of fibrinolysis is inhibited by plasminogen activator inhibitor type 1 (PAI-1) released from endothelium and platelets [26,29]. If the balance of fibrinolytic activators to their inhibitors is disturbed, this may result from the depletion of PAI-1 [45] and in patients with PAD, previous studies have demonstrated and increased fibrinolysis and fibrinolysis inhibition [46][47][48].…”
Section: Pathophysiology Of Thrombosis and Hemostasis In Peripheral Artery Diseasementioning
confidence: 99%
“…The activation of fibrinolysis is inhibited by plasminogen activator inhibitor type 1 (PAI-1) released from endothelium and platelets [26,29]. If the balance of fibrinolytic activators to their inhibitors is disturbed, this may result from the depletion of PAI-1 [45] and in patients with PAD, previous studies have demonstrated and increased fibrinolysis and fibrinolysis inhibition [46][47][48].…”
Section: Pathophysiology Of Thrombosis and Hemostasis In Peripheral Artery Diseasementioning
confidence: 99%
“…The underlying pathophysiological process in myocardial infarction and stroke originates from the formation of a fibrin clot and subsequent accumulation of fibrin in the blood vessels results in interference of blood flow and hence resulting in severe consequences such as irregular heartbeat, cardiac arrest, or death (Kietsiriroje et al., 2021). Currently, there exist several fibrinolytic agents used in fibrinolytic therapy to manage fibrin clot and restore blood flow such as urokinase and streptokinase enzymes which are often costly and carry undesirable side effects (Devaraj & Halami, 2021).…”
Section: Biological Activities In Fermented Shellfish Condimentsmentioning
confidence: 99%
“…Tissue factor released following vessel injury starts a cascade of reactions that culminate in the formation of thrombin that converts soluble fibrinogen into the insoluble fibrin network, which forms the skeleton of the thrombus. When the fibrin network forms, the fibrinolytic system is activated in order to limit thrombus extension, a process controlled by a fine balance between fibrinolytic and antifibrinolytic proteins, highlighting the intricacy of the system [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For the purpose of this review, we will adhere to the term 'plasmin inhibitor (PI)' throughout. PI is a direct inhibitor of plasmin by forming plasmin-antiplasmin (PAP) complexes, unlike other anti-fibrinolytic proteins that exert an indirect effect [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%